Editorial: Two Years of Growth and the Move to Continuous Publication (Journal of Economics, Law and Society, 2025)
As the Journal of Economics, Law and Society (JELS) (ISSN 3029‑3189) publishes Volume 2, Issue 2, we mark the completion of our second year as an international, peer‑reviewed platform dedicated to the intricate relationships between economics, law, and society, with a particular emphasis on Islamic finance and related interdisciplinary themes. This milestone coincides with an important strategic shift in our publishing model. Beginning with Volume 3, JELS will adopt a continuous publication policy, under which articles will be published online as soon as they complete peer review and production, rather than waiting for compilation into a full issue. This change reflects our commitment to timely scholarly communication, enhanced visibility for our authors, and greater accessibility for our global readership.Continuous publication has become an increasingly common model across academic journals because it reduces delays between acceptance and publication, allows research to be cited sooner, and supports a more dynamic flow of knowledge. For JELS, this model aligns closely with our mission to facilitate rapid, rigorous, and interdisciplinary dialogue among scholars, practitioners, and policymakers working at the intersection of law, economics, and society. While our archival structure of volumes and issues will remain, these will now be built progressively over time, as accepted articles are added in sequence. This evolution in our publishing practice is thus both operational and conceptual: it positions JELS as a responsive forum for emerging debates in areas that demand timely engagement, such as financial regulation, technological innovation, and institutional reform.